Struktur Sosial Komunikasi Organisasi dalam Perspektif Klasik, Humanis, Integratif, dan Kontemporer - Fitri Meliya Sari; Yusnadi Yusnadi; Hasrat Efendi Samosir (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2023)
This study aims to analyze the influence of social structure on organizational communication processes at the Faculty of Da'wah and Communication, UIN Ar-Raniry. This research uses a comparative study approach by comparing classical, human, integration, and contemporary perspectives in understanding the relationship between social structure and organizational communication. The research method used is comparative descriptive analysis, which involves collecting data through interviews, observation, and documentation studies. Respondents in this study consisted of lecturers, administrative staff, and students involved in organizational communication at the Faculty of Da'wah and Communication. The results showed that the existing social structure in the Faculty of Da'wah and Communication influenced the organizational communication process. In the classical perspective, hierarchical and authoritarian structures influence a more limited flow of information and communication. However, in a human perspective, a more democratic and participatory structure facilitates more open and mutually supportive communication. In an integration perspective, research shows that social structures that promote collaboration and reciprocity between organizational members increase communication effectiveness. On the other hand, in a contemporary perspective, research highlights the role of communication technology in changing organizational communication patterns, with the existence of social media and digital platforms that enable faster and wider communication.Penelitian ini bertujuan untuk menganalisis pengaruh struktur sosial terhadap proses komunikasi organisasi di Fakultas Dakwah dan Komunikasi, UIN Ar-Raniry. Penelitian ini menggunakan pendekatan studi komparatif dengan membandingkan perspektif klasik, human, integrasi, dan kontemporer dalam memahami hubungan antara struktur sosial dan komunikasi organisasi. Metode penelitian yang digunakan adalah analisis deskriptif komparatif, yang melibatkan pengumpulan data melalui wawancara, observasi, dan studi dokumentasi. Responden dalam penelitian ini terdiri dari dosen, staf administrasi, dan mahasiswa yang terlibat dalam komunikasi organisasi di Fakultas Dakwah dan Komunikasi. Hasil penelitian menunjukkan bahwa dalam perspektif klasik, struktur hierarkis dan otoriter mempengaruhi aliran informasi dan komunikasi yang lebih terbatas. Namun, dalam perspektif human, struktur yang lebih demokratis dan partisipatif memfasilitasi komunikasi yang lebih terbuka dan saling mendukung. Dalam perspektif integrasi, penelitian menunjukkan bahwa struktur sosial yang mempromosikan kolaborasi dan timbal balik antara anggota organisasi meningkatkan efektivitas komunikasi. Di sisi lain, dalam perspektif kontemporer, penelitian menyoroti peran teknologi komunikasi dalam mengubah pola komunikasi organisasi, dengan adanya media sosial dan platform digital yang memungkinkan komunikasi yang lebih cepat dan luas.Â